IMPROVING THE CORPORATE MANAGEMENT SYSTEM IN JOINT STOCK COMPANIES - Toychiyeva Ruhshona Arslonbek's daughter (American Journals Publishing, 2024)
In this article, the implementation of the corporate management system in joint-stock companies of Uzbekistan, as well as the development of proposals and recommendations for the improvement of the corporate management system in the activities of joint-stock companies.
Keywords: Corporate management, development strategy, joint-stock company, limited liability company, diversification, corporate code, strategic management.